Contemporary trends in pain therapy, sepsis and resuscitation - Kübler, Andrzej (Przewodnik Lekarza/Guide for GPs, 2007)
Pain therapy, severe infections and resuscitation are part of the knowledge in anaesthesiology. These topics also have interdisciplinary impact and are of interest for general practitioners. Opioids are increasingly used in noncancer chronic pain patients. They can be effective in some patients but a recent epidemiological study in Denmark showed that the long-term use of opioids does not improve the clinical course in chronic pain. Severe sepsis is a common syndrome and the main cause of mortality in intensive care units. Early diagnosis and fast therapeutic intervention can improve outcome. In ventricular fibrillation early external defibrillation is the most efficient method of treatment. It is also very important to conduct efficient external cardiac massage without breaks during the resuscitation period.